Polymorphism of the gene SHBG rs727428 associated with male infertility in a Vietnamese population - Nguyen, Thanh Thuy; Nguyen, Dang Thuy Linh; Nguyen, Thuy Duong (Vietnam Journal of Biotechnology, 2025)
Infertility is a complex disease, characterized by the incapability to achieve pregnancy after 24 months of regular unprotected sexual intercourse. Various studies have highlighted the role of sex hormone-related genes in contributing to the risk of male infertility. However, research on sex hormone-binding globulin (SHBG) – a glycoprotein involved in transporting sex hormones to target tissues, remains limited. Therefore, this study aimed to investigate whether SHBGrs727428 variant is associated with idiopathic male infertility in Vietnam. A total of 287 DNA samples (123 cases and 164 controls) were genotyped using polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) method. The results showed that genotype frequencies conformed to the Hardy-Weinberg equilibrium. Importantly, an association between SHBG rs727428 and male infertility was identified in three models: additive model (TT genotype, OR = 0.428, 95%CI 0.197 – 0.885, p-value = 0.021), dominant model (TT genotypes, OR = 0.473, 95%CI 0.229 – 0.928, p-value= 0.029) and allele model (T allele, OR = 0.680, 95% CI: 0.481-0.95, p-value = 0.028). This study enhances our understanding of the role of genetic factors in male infertility among the Vietnamese population.